The development and the wearability assessment of cliff: an automatized zipper - Mohamad Zairi, Baharom; Delbressine, Frank; Toeters, Marina; Feijs, Loe (International Journal of Mechanical Engineering and Robotics Research, 2018)
Cliff is a project which aims to develop an automatized zipper for the zipping and unzipping process. It is a response to the struggle by the elderly, people with physical disabilities and, ladies who have problems zipping back-zipper dresses. An iterative research through design approach was applied [1] to develop a working mechanism and prototype of Cliff. In order to assess the general comfort level of Cliff, the Comfort Rating Scales (CRS) method has been used. It measures the wearable comfort across six dimensions: emotion, attachment, harm, perceived change, movement and anxiety [2]. The user participatory design session has been designed and conducted to perform the study which includes a session of observation, prototype experience, a survey, and open questions. The test results show that the acceptance of the Cliff is satisfactory with all the levels of effect scoring at the lowest level. However, the findings also raised concerns about the stigmatisation effect. This study provided useful insight, opinions and, feedbacks which are essential to make Cliff ready for society.